Analysis of the geometric parameters of a solitary waves-based harvester to enhance its power output. (9th June 2017) - Rizzo, Piervincenzo; Li, Kaiyuan
Abstract: We present a harvester formed by a metamaterial, an isotropic medium bonded to the metamaterial, and a wafer-type transducer glued to the medium. The harvester conveys the distributed energy of a mechanical oscillator into a focal point where this energy is converted into electricity. The metamaterial is made with an array of granular chains that host the propagation of highly nonlinear solitary waves triggered by the impact of the oscillator. At the interface between the chains and the isotropic solid, part of the acoustic energy refracts into the solid where it triggers the vibration of the solid and coalesces at a point. Here, the transducer converts the focalized stress wave and the waves generated by the reverberation with the edges into electric potential. The effects of the harvester's geometric parameters on the amount of electrical power that can be harvested are quantified numerically. The results demonstrate that the power output of the harvester increases a few orders of magnitude when the appropriate geometric parameters are selected.